När en sjukdom skiftar namn: Om barnförlamning, polio och Heine-Medins disease - Axelsson, Per (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2002)
With examples from the history of polio this study examines the creation of disease terminology. When the epidemologist Ivar Wickman in 1907 discovered that poliomyelitis was an infectious disease and that it could be transmitted by healthy carriers, he proposed a new term for the disease, Heine-Medins disease. He thereby dedicated the disease to his mentor, the paediatrician Karl Oskar Medin, and the German orthopaedist Jacob von Heine. Contemporary medical scientists accepted his proposal and during the 1910s a great amount of work on Heine-Medins disease was published. Moreover the study shows that the term Heine-Medins disease did not reach the public sphere. The results are related to Ludwik Flecks framework of "thought-styles".